Strong, beautiful and modern : national fitness in Britain, New Zealand, Australia and Canada, 1935-1960 - Macdonald, Charlotte (UBC Press, 2013)
In this highly original account, Charlotte Macdonald shows how governments became convinced they must encourage citizens to be healthier and more active, and how these efforts reinforced the cultural ties of the Empire. Alongside these state-sponsored efforts was a growing emphasis from business, the medical establishment, and popular culture on the importance of having "a better body."
Originally published: Wellington, New Zealand : Bridget Williams Books Limited, 2011.
Keywords: Physical fitness -- Government policy -- Canada -- History -- 20th century.; Physical fitness -- Government policy -- Australia -- History -- 20th century.; Physical fitness -- Government policy -- New Zealand -- History -- 20th century.; Physical fitness -- Government policy -- Great Britain -- History -- 20th century.; Exercise.; Physical Fitness -- history; Exercise; Health Policy -- history; Health Promotion -- history; Body Image; History, 20th Century; United Kingdom; Australasia; Canada; Condition physique -- Politique gouvernementale -- Grande-Bretagne -- Histoire -- 20 siècle.; Condition physique -- Politique gouvernementale -- Nouvelle-Zélande -- Histoire -- 20e siècle.; Condition physique -- Politique gouvernementale -- Australie -- Histoire -- 20e siècle.; Condition physique -- Politique gouvernementale -- Canada -- Histoire -- 20e siècle.; Exercice.; Médecine -- Histoire -- 20e siècle.; HEALTH & FITNESS -- Exercise.; Physical fitness -- Government policy; Australia; Great Britain; New Zealand; 1900-1999; History